2017
DOI: 10.29252/ijrm.15.11.703
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome microdeletions frequency in idiopathic azoospermia, oligoasthenozoospermia, and oligospermia

Abstract: Background:Genetic factors are candidates for about 30% of male infertility with sperm production-related abnormalities. Y chromosome microdeletions are responsible for around 10% of male infertility. These microdeletions generally occur in azoospermia factor on the Yq. That is often associated with the quantitative reduction of sperm.Objective: The aim of this cross-sectional study was to determine the frequency of Yq microdeletions among idiopathic azoospermic, oligoasthenozoospermic, and oligospermic men in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Studies have shown that the levels of sex hormones, such as LH, FSH, and testosterone were significantly higher in infertile men in comparison with healthy men. These hormonal changes were much more seen in azoospermic men than in other infertile subgroups (36,37). These results suggest that the FSH, LH, prolactin, and testosterone levels cannot predict microdeletions in AZF in infertile men.…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown that the levels of sex hormones, such as LH, FSH, and testosterone were significantly higher in infertile men in comparison with healthy men. These hormonal changes were much more seen in azoospermic men than in other infertile subgroups (36,37). These results suggest that the FSH, LH, prolactin, and testosterone levels cannot predict microdeletions in AZF in infertile men.…”
Section: Discussionmentioning
confidence: 74%
“…Diferentemente desse estudo, há relatos de que o cigarro influência na qualidade do sêmen (DAI, et al, 2015;ASARE-ANANE, et al, 2016;SANSONE, et al, 2018) e nos níveis dos hormônios sexuais (BASSEY, et al, 2018). Gholami et al (2017), também citam a potencial associação do cigarro com a microdeleção na região AZF. Bundhun et al (2019) demonstraram no seu estudo de meta análise que o tabaco está fortemente associado a um baixo número de espermatozoides, mas em um total de 16 estudos pesquisados por eles, o número de homens inférteis não fumantes foi analisado em 11 estudos, e fumantes foram de apenas 05 e 50% dos que não consumiam álcool eram azoospermicos, assim como esse estudo.…”
Section: Materiais E Métodosunclassified
“…The Y chromosome microdeletions are the second genetic cause of male infertility after Klinefelter syndrome (6). The frequency of Y chromosome microdeletions was 6.17% in Chaharmahal and Bakhtiari Province (7). Generally, men with karyotype 47, XYY are fertile although this karyotype is much frequently observed in infertile men.…”
Section: Introductionmentioning
confidence: 99%